Encanto [videorecording (DVD)] - Miranda, Lin-Manuel, 1980- (Disney DVD., 2022)
The Madrigals live hidden in the mountains of Colombia, in a magical house, in a vibrant town, in a wondrous, charmed place called an Encanto. The magic of the Encanto has blessed every child in the family with a unique gift from super strength to the power to heal, every child except one--Mirabel. But when she discovers that the magic surrounding the Encanto is in danger, Mirabel decides that she, the only ordinary Madrigal, might just be her exceptional family's last hope.